Amateur radio based weather station - Lim, Chia Cheen (Universiti Malaysia Sarawak, UNIMAS, 2006)
Weather i s an important factor in daily activities and economic sectors, such as tourism and agriculture. As easy as it may seems to be to get a weather report from mass media, it is difficult to get local weather status at a specific area, which may be differed fr om other places at a few kilometers away. In rural areas, where telecommunication and transportation are hard to establish, local weather report is even harder to come by. This project presents an alternative using weather station that based on amateur rad io as its communication tool. In this final year project report, a detailed description about project concept and technical aspect is given. Based on the methodology as mentioned in the report, the outcome of the project is described. At the end of this re port, recommendations are made to further improve the project.